PENGARUH KEMAMPUAN KERJA, PENGALAMAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI NEGERI SIPIL (PNS) PADA KANTOR KECAMATAN BAHODOPI KABUPATEN MOROWALI - Zainal Zainal (Katalogis, 2016)
The aims of this research are: 1) to determine and analyze the influence of work ability, work experience, and work discipline on civil servants’performance at Bahodopi District Office, Morowali Regency; 2) to determine and analyze the influence of work ability on civil servants’ performance; 3) to determine and analyze the influence of work experience on civil servants’ performance; 4) to determine and analyze the influence of work discipline on civil servants’ performance. Type of the research is explanative that shows the causalities between independent and dependent variabels, and consist of 30 respondents who selected through census method. Based on multiple linear regressions analysis test, the research concludes that: 1) work ability, work experience, and work discipline simultaneously influence civil servants’ performance at bahodopi district office, Morowali Regency; 2) work ability significantly and positively influence civil servants’ performance; 3) work experience significantly and positively influence civil servants’ performance; 4) work discipline significantly and positively influence civil servants’ performance.